Pengaruh Pemanfaatan E-Commerce, Harga, dan Promosi Terhadap Minat Beli Konsumen ( Studi Pada Pelanggan Toko Roti Hilda Bakery Kota Batu) - Rosaliana, Hilda Angeningtyas; Priyono, Achmad Agus; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine and explain the effect of e-commerce utilization, price, and promotional intensity on consumer buying interest in bakeries in Batu City, a case study of customers of Hilda Bakery in Batu City. The number of samples that were successfully collected was 75 respondents. While the analysis tool used is Multiple Linear Regression using SPSS. The results of this study are e-commerce, price, and promotional intensity simultaneously affect purchasing decisions and e-commerce has a significant positive effect on consumer buying interest, price has an effect on consumer buying interest while promotional intensity has no significant effect on consumer buying interest. Keywords: E-commerce, Price, Promotion Intensity, Consumer Purchase Intention